NUTRITIONAL STATUS ASSESSMENT OF FEMALE CANCER PATIENTS IN COCHIN, KERALA - RASHMI H. POOJARA* and ANOL THOMAS, (The Journal of Research ANGRAU, 2021)
The study envisaged the assessment of nutritional, functional status and, Quality of Life (QoL)among selected female cancer patients undergoing cancer therapy. The findings suggested thatbreast cancer was the leading type of cancer and the majority of the patients were in the terminalstages of cancer. The Subjective Global Assessment (SGA) revealed that the majority of subjectsbelonged to the mildly-moderately nourished category. All the study subjects had an inadequatenutrient intake concerning energy, protein, fat, calcium, iron, and ascorbic acid. A statistically significantdifference was evident between the actual and suggested nutrient intake. The mean values of physical,social/family, emotional and functional well-being using the FACT-G scale were computed to be 16.6,18.8, 11.2, and 10.8, respectively showing that QoL was poor among study subjects, thus, impactingcancer therapy. The nutrient intake of the patients was compared with SGA grading and it was foundthat there was a statistically significant difference in the nutrient intake among the patients belongingto different nutritional status categories with the lowest intake in the severely malnourished